§ 1.

      5. f(x) = 0 , :

 

5.01.

 f(x) = 26 x5 3x4 2x2 + 4x 3, x0 = 2;

5.02.

 f(x) = 47 3x6 + 2x4 3x3 4x + 2, x0 = 2;

5.03.

 f(x) = 8 3x7 + 4x4 + 2x3 3x2 + 1, x0 = 3;

5.04.

 f(x) = i6 + 2x5 (2 + 3i)x3 + x2 ix + 5, x0 = i;

5.05.

 f(x) = 27 3x6 + ix5 + (2 i)x3 3x2 + ix i, x0 = 1 i;

5.06.

 f(x) = 6 + ix5 + (2 i)x4 ix3 + (2 + 3i)x2 + 3ix + 1, x0 = 1 + i;

5.07.

 f(x) = 37 2x5 + 6x3 4x2 3x + 1, x0 = 3;

5.08.

 f(x) = i6 + (3 i)x5 + (2 3i)x4 + ix3 + (1 + i)x2 3ix + 6, x0 = i 1;

5.09.

 f(x) = 25 x4 + 2x3 + x + 2 + 3i, x0 = 1 + 4i;

5.10.

 f(x) = 5 + (2 2i)x4 ix3 + 4x2 ix + 2 i, x0 = 2 + i;

5.11.

 f(x) = 45 (2 + 5i)x4 +(4 3i)x3 +(3 i)x2 +(6 + 7i)x + 7 2i, x0 = 1 + 2i;

5.12.

 f(x) = 5 + (1 + 2i)x4 (1 + 3i)x3 + 7x 6 + i, x0 = 2 i;

5.13.

 f(x) = 25 + (1 + i)x4 ix3 + 2x2 + 2, x0 = 4 + i;

5.14.

 f(x) = 78 2x5 + 4x4 3x3 + 4x 10 + 4i, x0 = 5;

5.15.

 f(x) = 29 x7 x3 + 2x2 1, x0 = 2i;

5.16.

 f(x) = 28 ix6 ix5 + 2x3 x i, x0 = 2i;

5.17.

 f(x) = 9 x7 3x6 4x5 + 2x2 4, x0 = 2;

5.18.

 f(x) = 36 4x5 ix3 + ix2 + 7x + i, x0 = 1 + i;

5.19.

 f(x) = 46 ix4 + 2x2 (3 + i)x 4, x0 = 2 i;

5.20.

 f(x) = i5 + 2x4 (3 + i)x2 4x 2 + i, x0 = 2 + i;

5.21.

 f(x) = i5 + (i + 1)x4 + ix3 + (1 2i)x2 (1 + i)x + 1, x0 = 1;

5.22.

 f(x) = 45 x4 + 2x2 7x + 10, x0 = 2;

5.23.

 f(x) = 5 + (1 + i)x4 2x2 + (1 + 3i)x + i, x0 = 3i;

5.24.

 f(x) = 66 ix5 + 4x4 + 3x3 ix2 + 2ix 7, x0 = 1 i;

5.25.

 f(x) = 26 ix5 (2 + i)x3 + 4x2 3x + 6 + 2i, x0 = 1+ i;

5.26.

 f(x) = 37 + 2ix6 (1 + 2i)x4 + 2ix2 + 4x 3 3i, x0 = 1 2i;

5.27.

 f(x) = 35 (1 + i)x4 ix3 + (1 + 2i)x2 + 3ix + 4 + i, x0 = 2 + i;

5.28.

 f(x) = 26 + 2ix4 2ix3 (3 i)x2 + (i + 1)x + 5, x0 = 2 3i;

5.29.

 f(x) = 47 + 3x5 (1 + i)x3 (2 3i)x + 4 + 6i, x0 = 4i;

5.30.

 f(x) = 8 + (2 i)x6 2x5 ix3 + (2 + 3i)x2 + 4 3i, x0 = 1 + i;

5.31.

 f(x) = 38 4ix7 + 3x5 ix4 + 3x2 (1 i)x + 7, x0 = 2i;

5.32.

 f(x) = 27 (3 + i)x6 + ix4 2x3 ix2 3, x0 = 2 i;

5.33.

 f(x) = 46 + (1 i)x5 ix4 + (1 + i)x3 2ix + 3 i, x0 = 1 i;

5.34.

 f(x) = 29 3x8 3x6 4x3 + 2x2 4x + 6, x0 = 3;

5.35.

 f(x) = 39 4x8 + 2x7 4x4 2x3 + 6x 12, x0 = 2;

5.36.

 f(x) = i6 2ix5 + 3x4 (1 i)x3 + 2ix2 6x + 3, x0 = 2 i.

\..\

                              Copyright © 2008-2009 ..   . .